Pengembangan Strategi Keuangan Untuk Meningkatkan Kesejahteraan Pengelola Pada Toko Sembako Waru, Sidoarjo - Azza Nuha Nisrina (CV. ITTC INDONESIA, 2024)
This research discusses the financial strategies of the Sembakol Sidoarjo store. Improving manager security and achieving broader business goals requires proper market analysis, product differentiation, product positioning, and financial resource management. The government has developed the People's Welfare Index (IkraR) and social protection programs to improve people's welfare. Effective marketing strategies include increased education, motivation, and a supportive environment. Analysis of the internal and external environment includes an assessment of the strengths, weaknesses, opportunities and threats (SWOT) that influence the Waru Sembako business. Effective financial strategies include better financial management and require consumers to make a 50% down payment. Explaining marketing and financial strategies is essential to increasing the overall success of your business. In this way, the Sembakwar Branch can improve manager safety and increase business success.